Cultural Beliefs and the Organization of Society: A Historical and Theoretical Reflection on Collectivist and Individualist Societies - Greif, Avner (Journal of Political Economy, 1994)
This paper integrates game-theoretical and sociological concepts to conduct a comparative historical analysis of the relations between culture and institutions. It indicates the importance of culture, and in particular cultural beliefs, in determining institutions, in institutional path dependence, and in forestalling intersociety successful adoption of institutions. Examination of institutional change in two premodern societies from the Muslim and the Latin worlds yields that their distinct institutional structures resemble those found by social psychologists to differentiate contemporary developing and developed economies. This suggests the historical importance of distinct cultures and the related societal organizations in economic development. Copyright 1994 by University of Chicago Press.